Klasifikasi Kelayakan Beras Menggunakan Metode Laplacian of Gaussian - Abdullah, Khabib; Riadi, Aditya Akbar; Evanita, E (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Rice is a staple food for some Indonesians, but lately there is a lot of rice that is not fit for consumption/not worth selling, but is still being traded in the market by irresponsible people. With the development of technology that is growing rapidly, it is directly proportional to the development of information systems. The problem here is that the rice we consume, the quality is determined by the price, even though the price does not necessarily guarantee the quality of the rice. From these problems, a system is made that can classify rice. This research takes a picture of rice setra ramos and then the image is processed by the image, according to the size of the border and the color that has been determined. That is 0.7 cm the size of good rice and clean white or yellow-brown in color. The result of image processing is in the form of rice classification, namely good rice, medium rice, and bad rice. In thos study, using the Python programming language and the opencv library as image processing. With this system, it is hoped that it can help people choose rice that is suitable for consumtion.